2013
DOI: 10.1186/1472-6963-13-315
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the essential dimensions of the primary health care services in six localities of Bogota–Colombia: a cross-sectional study

Abstract: BackgroundThe high segmentation and fragmentation in the provision of services are some of the main problems of the Colombian health system. In 2004 the district government of Bogota decided to implement a Primary Health Care (PHC) strategy through the Home Health program. PHC was conceived as a model for transforming health care delivery within the network of the first-level public health care facilities. This study aims to evaluate the performance of the essential dimensions of the PHC strategy in six locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…They found that the global performance index was rated as good for all interviewees. The weakest dimensions were the family focus and community orientation; the distribution of financial resources; and, accessibility [51]. …”
Section: Resultsmentioning
confidence: 99%
“…They found that the global performance index was rated as good for all interviewees. The weakest dimensions were the family focus and community orientation; the distribution of financial resources; and, accessibility [51]. …”
Section: Resultsmentioning
confidence: 99%
“…Being a particular case, Bogotá provides PHC services from the public sphere. It combines promoting, preventive, curative and rehabilitative actions in its comprehensive approach [32]. Thus, themes related to disease treatment in the logic of the groups studied corresponded to other service levels or they are explicit objectives of the private market.…”
Section: Discussionmentioning
confidence: 99%
“…Colombia, although already having isolated PHC experiences in its various regions, has recently experienced a national consolidation of policies to strengthen the health system through PHC and emphasizes health promotion in the 10-year public health plan [30]. Bogotá, the capital city, has been a reference point: its renovation started in 2004 and the implementation of the Collective Intervention Plan (Spanish acronym: PIC) acts through a structure that combines management, surveillance, and operation of actions in real life scenarios within the public health field [32]. These, in turn, relate to the environments where people live, grow, and interact: family, school, community, workplace, and the institutions that provide health care.…”
Section: Methodsmentioning
confidence: 99%
“…19,20,21 Even in developed countries, patients are more dissatisfied with healthcare within systems where fragmentation is greater. 22 To address fragmentation, there needs to be greater service integration of essential MCWH care.…”
Section: Discussionmentioning
confidence: 99%